DISTURBIOS DO SONO EM PROFISSIONAIS DA SAÚDE NO SURTO DE COVID - 19:: UMA REVISÃO INTEGRATIVA DA LITERATURA - Steven Philippart, Kevin; Sayuri Shiraishi, Letícia; Domingos Ribeiro, Lucas; Ventura Tauyr, Luciana; Tadeu Guardia Júnior, Marcos; Espirito Santo Campos, Nathalia (Health and Society, 2021)
Coronaviruses (CoVs) are enveloped viruses with a crown aspect. The speed of COVID-19’s spread has interfered in the daily lives of billions of people on the planet in several aspects, such as social, economic, scientific and medical. The infection affects the upper respiratory tract, predominantly. The health team is vulnerable to the contagion of the virus and can evolve negatively to sleep disorders. This way, the investigation of the relationship between sleep disorders in health professionals in the face of the COVID-19 pandemic is necessary and becomes the main objective of this review, especially regarding to the quality of sleep, seeking to determine correlations between the occurrence of the pandemic around the world and sleep disorders caused by it. An integrative literature review was carried out, following the exploratory character of a qualitative approach. 735 articles were found, 78 met the inclusion criteria, 16 articles were selected for careful reading and in full and, finally, 7 articles were considered pertinent and studied. Thus, the assessment of sleep quality was analyzed through several screening questionnaires. Female representativeness was 61% and male 39% of the total number of participants. The average age of the sample was 28-40 years, being 35 years the age of emphasis. Nursing professionals were the most affected category by insomnia, being mentioned in four studies (57%). Numerous factors can contribute to the quality of sleep of health professionals, such as physical exhaustion due to social isolation, the use of personal protective equipment for many hours, concerns about the family and fear of contamination. The research was performed with adequate scientific rigor, with acquisition of new knowledge and, toward analysis, new coping strategies were suggested by the authors.